2022
DOI: 10.1021/jacs.1c12622
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Amination of Phenols with Amines

Abstract: Given the wide prevalence and ready availability of both phenols and amines, aniline synthesis through direct coupling between these starting materials would be extremely attractive. Herein, we describe a rhodium-catalyzed amination of phenols, which provides concise access to diverse anilines, with water as the sole byproduct. The arenophilic rhodium catalyst facilitates the inherently difficult keto–enol tautomerization of phenols by means of π-coordination, allowing for the subsequent dehydrative condensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 65 publications
(26 reference statements)
0
22
0
Order By: Relevance
“…However, the direct amination of phenol derivatives, although very attractive, is usually difficult and requires harsh conditions and expensive transition-metal catalysts to achieve Scheme 1 Process for the preparation of MDI (A) and synthetic pathway of BGI (B) effective dearomative "hydrogen-borrowing strategy" (scheme 3A). [25][26][27][28][29][30] Scheme 2 Synthesis of BGF according to literature procedure 23 23 [25][26][27][28][29][30] Moreover, the substrate scope of such transformations is somewhat limited, especially when using ammonia as the nitrogen nucleophile. 26,27 Alternatively, the amination of phenols via transition-metal-free Smiles rearrangement has also been described (scheme 3B).…”
Section: Resultsmentioning
confidence: 99%
“…However, the direct amination of phenol derivatives, although very attractive, is usually difficult and requires harsh conditions and expensive transition-metal catalysts to achieve Scheme 1 Process for the preparation of MDI (A) and synthetic pathway of BGI (B) effective dearomative "hydrogen-borrowing strategy" (scheme 3A). [25][26][27][28][29][30] Scheme 2 Synthesis of BGF according to literature procedure 23 23 [25][26][27][28][29][30] Moreover, the substrate scope of such transformations is somewhat limited, especially when using ammonia as the nitrogen nucleophile. 26,27 Alternatively, the amination of phenols via transition-metal-free Smiles rearrangement has also been described (scheme 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Deng et al 131 demonstrated the potential of metal phosphides by successfully catalyzing the amination of furan alcohols. Shi et al 132 reported an efficient rhodium-catalyzed direct amination of phenols with amines without activating reagents or reductants/oxidants. Recently, Li et al 66 demonstrated a new strategy for the directional preparation of pyrimidines from lignin β-O-4 model compounds without transition-metal catalysis, using NaOH to facilitate a one-pot multi-component cascade reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The methodologies pertaining to this particular transformation have largely employed conventional nucleophilic substitution reactions 3 and transition metal-catalyzed C–N cross-coupling reactions. 4 However, these protocols suffer from serious drawbacks such as low yield, substrate specificity, 5 and many other limitations. 6 In the past few years, catalytic C(sp 2 )–H amination utilizing transition-metal as well as metal-free conditions using suitable directing groups has been reported.…”
Section: Introductionmentioning
confidence: 99%